Surveillance for colorectal cancer and chemoprevention in ulcerative and Crohn's colitis: The need for clinical strategies to increase effectiveness. Issue 5 (11th April 2019) - Farrukh, Affifa; Mayberry, John F
Abstract : This review considers why current strategies for surveillance and the prevention of colorectal cancer as a long‐term complication are ineffective. The role of endoscopists, pathologists, and patients are investigated. Colorectal cancer is linked to poor compliance with therapy, and attention may be better directed at improving adherence to treatment than strengthening current surveillance programs. Clearly, 5‐ASA compounds, particularly mesalazine, are the most appropriate agents to choose, but there may also be a place for the daily intake of folic acid. Currently, the evidence in support of ursodeoxycholic acid is mixed, and it cannot be recommended, in general, to patients for the prophylaxis of colorectal cancer risk. An alternative approach through better concordance with medications is considered. The situation in Crohn's colitis is less clear. Although the risk of colorectal cancer mirrors that in ulcerative colitis, there are no published community‐based studies that exclusively assess the effects of surveillance on the early detection of cancer, and the benefits of 5‐ASA compounds in treatment seem less certain than in ulcerative colitis. In addition, there have been no assessments of the effects of any medications on cancer risk in Crohn's disease. Abstract : Screening for early cancer in ulcerative and Crohn's colitis does not work. There is good evidence that 5‐ASA compounds do work to reduce cancer risk. This paper looks at ways to ensure compliance with this therapy.